2015
DOI: 10.1373/clinchem.2014.236679
|View full text |Cite
|
Sign up to set email alerts
|

Importance and Impact of Preanalytical Variables on Alzheimer Disease Biomarker Concentrations in Cerebrospinal Fluid

Abstract: BACKGROUND Analyses of cerebrospinal fluid (CSF) biomarkers (β-amyloid protein, total tau protein, and hyperphosphorylated tau protein) are part of the diagnostic criteria of Alzheimer disease. Different preanalytical sample procedures contribute to variability of CSF biomarker concentrations, hampering between-laboratory comparisons. The aim of this study was to explore the influence of fractionated sampling, centrifugation, freezing temperature, freezing delay, and freeze–thaw cycles on CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
62
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 28 publications
3
62
0
1
Order By: Relevance
“…In line with this, CSF t-Tau and p-Tau levels were reported to be significantly lower when CSF samples were frozen at −20°C instead of −80°C [16,34].…”
Section: Storage Conditionssupporting
confidence: 62%
“…In line with this, CSF t-Tau and p-Tau levels were reported to be significantly lower when CSF samples were frozen at −20°C instead of −80°C [16,34].…”
Section: Storage Conditionssupporting
confidence: 62%
“…However, no differences in A␤1-42 and T-tau concentrations between lumbar CSF fractions were found, consistent with previous studies (9 ) and also true for P-tau181P. Comparison of centrifuged and noncentrifuged samples from the same fractions revealed that centrifugation had no effect on CSF biomarker concentrations in macroscopically non-blood-contaminated samples (8 ). The practical implication is that centrifugation is not required for CSF biomarker analyses, and this likely is true, as the authors discuss, even when CSF is contaminated with blood (8 ).…”
supporting
confidence: 91%
“…Le Bastard et al concluded that it is possible to collect CSF in a single large volume or several smaller volumes from their observation that the total volume of CSF collected does not affect the concentrations of tau and amyloid proteins (8 ). Fractionated sampling of lumbar CSF has been postulated to be important, given that brain-derived proteins usually show a rostrocaudal concentration gradient, with higher concentrations in ventricular CSF compared to lumbar CSF, thereby implying that different volumes or fractionated sampling could generate differences in CSF biomarker concentrations.…”
mentioning
confidence: 99%
See 2 more Smart Citations